2006
DOI: 10.1104/pp.105.074419
|View full text |Cite
|
Sign up to set email alerts
|

Cosecretion of Protease Inhibitor Stabilizes Antibodies Produced by Plant Roots

Abstract: A plant-based system for continuous production of monoclonal antibodies based on the secretion of immunoglobulin complexes from plant roots into a hydroponic medium (rhizosecretion) was engineered to produce high levels of singlechain and full-size immunoglobulins. Replacing the original signal peptides of monoclonal antibodies with a plant-derived calreticulin signal increased the levels of antibody yield 2-fold. Cosecretion of Bowman-Birk Ser protease inhibitor reduced degradation of the immunoglobulin compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 35 publications
(35 reference statements)
0
64
0
1
Order By: Relevance
“…Xu et al (2004) have reported that the heterogeneous expression of a PI from nightshade (SaPIN2a) in transgenic lettuce resulted in the inhibition of plant endogenous trypsin-like and chymotrypsin-like activities, suggesting that the heterogeneous expressed PIs could be exploited in the protection of recombinant protein production in transgenic plants. Komarnytsky et al (2006) further confirmed that co-secretion of soybean Bowman-Birk Ser protease inhibitor reduced degradation of the immunoglobulin complexes in the secretion pathway of transgenic tobacco roots and increased antibody production. Rivard et al (2006) also found that transgenic potato expressing either tomato cathepsin D inhibitor (CDI) or bovine aprotinin showed decreased levels of cathepsin D-like and ribulose 1,5-bisphosphate carboxylase/ oxygenase hydrolysing activities in vitro, and the decreased turnover rates of the selection marker protein neomycin phosphotransferase II (NPT II).…”
Section: Co-expression Of Proteinase Inhibitors In Plant Bioreactorsmentioning
confidence: 54%
See 1 more Smart Citation
“…Xu et al (2004) have reported that the heterogeneous expression of a PI from nightshade (SaPIN2a) in transgenic lettuce resulted in the inhibition of plant endogenous trypsin-like and chymotrypsin-like activities, suggesting that the heterogeneous expressed PIs could be exploited in the protection of recombinant protein production in transgenic plants. Komarnytsky et al (2006) further confirmed that co-secretion of soybean Bowman-Birk Ser protease inhibitor reduced degradation of the immunoglobulin complexes in the secretion pathway of transgenic tobacco roots and increased antibody production. Rivard et al (2006) also found that transgenic potato expressing either tomato cathepsin D inhibitor (CDI) or bovine aprotinin showed decreased levels of cathepsin D-like and ribulose 1,5-bisphosphate carboxylase/ oxygenase hydrolysing activities in vitro, and the decreased turnover rates of the selection marker protein neomycin phosphotransferase II (NPT II).…”
Section: Co-expression Of Proteinase Inhibitors In Plant Bioreactorsmentioning
confidence: 54%
“…Even though various successful expression systems have been reported in plant bioreactors including the use of seed protein storage vacuoles or oil-bodies, cell suspension cultures, root exudates and chloroplasts (Borisjuk et al, 1999;Conrad and Fiedler, 1998;Downing et al, 2006;Giddings et al, 2000;Komarnytsky et al, 2000;van Rooijen and Moloney, 1995), a critical problem in plant bioreactors thus far is the low yield of the recombinant proteins due to the degradation system in plants. As a result, one of the possible solution or improvement is to co-express the target protein together with protease inhibitor to protect the protein from being degradation and thus leading to high yield of the recombinant proteins in transgenic plants (Kim et al, 2007;Komarnytsky et al, 2006;Rivard et al, 2006;Xu et al, 2004). Figure 1 shows several representative plant organelles for protein compartmentation of pharmaceuticals and their targeting or delivery strategies in plant bioreactors, where Golgi-bypassing of recombinant proteins to reach seed protein storage vacuole (PSV) would avoid unwanted plant-specific complex glycan modification.…”
Section: Introductionmentioning
confidence: 99%
“…33 Several research groups have employed different strategies to attempt to increase the yield of rhizosecreted PMP, with varying results. These include the use of a root promoter 30 or a plant signal sequence, 34 A. rhizogenes to induce hairy roots on transgenic tobacco plants 35 and co-expression of the Bowman-Birk Ser protease inhibitor. 34 In our group we investigated the effects of a range of plant growth regulators, including α-naphthalene acetic acid (NAA) on rhizosecretion of Guy's 13 mAb and CV-N. 33 At the molecular level, auxins, such as NAA, promote cell elongation, by increasing cell wall extensibility via the breaking of hydrogen bonds between the polysaccharide components of the cell wall.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…However, research on the use of transgenic plants expressing a protease inhibitor as a production system for recombinant proteins is still very limited. Komarnytsky et al [29] expressed and cosegregated a soybean Bowman-Birk trypsin inhibitor stabilizing recombinant antibodies secreted by transgenic tobacco roots. Rivard et al [38] recently described a 'mouse trap' strategy including either a tomato cathepsin D inhibitor or bovine aprotinin, which are active against trypsin and chymotrypsin, for protein production using ribulose 1,5-bisphosphate carboxylase/oxygenase as a target enzyme.…”
Section: Introductionmentioning
confidence: 99%